PROTECTION OF PATIENTS' RIGHTS IN HOSPITAL LEGAL LIABILITY EXPANSION SCHEME - Gunawan Widjaja (INJOSEDU: International Journal of Social and Education, 2025)
The protection of patients' rights is an important focus in improving the quality of health services in hospitals. This research explores how the expansion of hospitals' legal responsibilities can serve to protect patients' rights more effectively. In this context, hospitals are not only responsible for medical practices, but are also obliged to comply with the legal framework governing the right to information, humane treatment, and quality healthcare. This study emphasises that synergies between legal regulations, internal hospital policies, and ethical practices, play a crucial role in realising safety and protection for patients. The results highlight the importance of the active involvement of hospitals, the government, and patients themselves to ensure that patients' rights are respected and protected, so that public trust in the healthcare system can be enhanced.